Risk factors associated with progressive lacunar strokes and benefit from dual antiplatelet therapy - Berberich, Anne; Tunkl, Christine; Herweh, Christian; Hielscher, Thomas; Reiff, Tilman; Bendszus, Martin; Gumbinger, Christoph; Ringleb, Peter A. (European journal of neurology, 2020)
Background and purpose - Early neurological deterioration (END) occurs in 20%-30% of patients with lacunar stroke and challenges their clinical management. This retrospective cohort study analyzed cli...